NARRATIVE REVIEW TANAMAN YANG BERPOTENSI SEBAGAI IMMUNOMODULATOR - Winda Trisna Wulandari; Gina Nur Fitria Mulyana Putri; Hisni Nurul Fajri; Indah Alvina Damayanti; Silvia Rahmawati; Dina Lestari (JFL : Jurnal Farmasi Lampung, 2021)
COVID-19 (Coronavirus Disease-2019) is an infectious disease caused by the acute respiratory syndrome SARS-CoV-2. Currently, the COVID-19 disease outbreak is experienced by various countries around the world, including Indonesia. In overcoming it, there are several ways of deterrence that can be done, such as by increasing the body's immunity. During the COVID-19 pandemic, maintaining immunity is something that needs to be considered. In addition to vitamins, herbal plants that have the potential as immunomodulators can also be consumed. Therefore, through efforts to improve theimmune system, this review aims to obtain plants that have the potential as immunomodulators to enhance the immune system during the COVID-19 pandemic. The research method in the review used journals available online at Google Scholar with Sinta or Garuda accredited journals. The main focus of this review is herbal plants that have a role as an immunomodulator that can improve the body's immune system. The journals used are journals published in 2011-2021 with inclusion criteria, namely using Indonesian or English about plants that have the potential as immunomodulators, then the journalsobtained are analyzed. The results obtained were 30 types of plants that have potential as immune system enhancers including Dayak Onion Tubers, Papaya Leaves, Kecombrang Fruits, Pineapple Fruits, Kesambi, Soursop Leaves, Purslane, Garlic, Dates, Celery Leaves, Andaliman, Mahkota Dewa Fruit. , Moringa, Meniran, Noni Fruit, Gotu Kola, Sambiloto, Kiseureuh, Javanese Chili, Tempuyung Leaves, Basil Leaves, Ceplukan, Seaweed, Neem Leaves, Red Betel Leaf, Salam Leaves, Guava, Turmeric, Lime and Red Ginger Rhizome with compounds that act as flavonoids, alkaloids, saponins, triterpenoids,xeronin, tannins, quersentin, -tocopherol, lycopene, catechins, diterpenoids, deoxyandrographolide, andrographolide, epicatechin isothiocyanate and curcumin. Keywords: COVID-19, Potency of Immumodulator Plants, Flavonoids